Atraumatic Acute Limb Ischemia: Clinical Presentation, Classification, Assessment and Management- A Review - Nalaka Gunawansa (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
Acute Limb Ischaemia (ALI) can be a devastating clinical emergency with potentially life or limb threatening consequences. The commonest aetiologies of ALI are traumatic, embolic or thrombotic. While traumatic ALI is fairly obvious in the trauma victim, embolic and thrombotic ALI may mimic other clinical conditions such as neurological disease which may cause delays in diagnosis. Immediate diagnosis, accurate assessment of limb viability and urgent intervention when needed play a crucial role in salvaging the affected limb and preventing a major amputation. Delay in diagnosis and intervention causes irreversible muscle ischaemia leading to eventual limb loss and potential systemic organ dysfunction due to associated lactic acidosis and other toxins.